2019
DOI: 10.1016/j.jmmm.2019.02.075
|View full text |Cite
|
Sign up to set email alerts
|

Building traps for skyrmions by the incorporation of magnetic defects into nanomagnets: Pinning and scattering traps by magnetic properties engineering

Abstract: In this work we have used micromagnetic simulations to report four ways to build traps for magnetic skyrmions. Magnetic defects have been modeled as local variations in the material parameters, such as the exchange stiffness, saturation magnetization, magnetocrystalline anisotropy and Dzyaloshinskii-Moriya constant. We observe both pinning (potential well) and scattering (potential barrier) traps when tuning either a local increase or a local reduction for each one of these magnetic properties. It is found tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 96 publications
(131 reference statements)
2
29
0
2
Order By: Relevance
“…(1). It is worth mentioning that the present work explores the results of a previous work [47], where our team has reported that spatial variations on the material parameters of the ferromagnetic medium (exchange stiffness, saturation magnetization, magnetocrystalline anisotropy and Dzyaloshinskii-Moriya constants) can work as traps for pinning and scattering magnetic skyrmions. Fig (a) highlights that the majority of the nanowire's magnetic moments is going out of the plane of the figure except at the core of the skyrmion (red region), where they are pointing in the opposite direction.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…(1). It is worth mentioning that the present work explores the results of a previous work [47], where our team has reported that spatial variations on the material parameters of the ferromagnetic medium (exchange stiffness, saturation magnetization, magnetocrystalline anisotropy and Dzyaloshinskii-Moriya constants) can work as traps for pinning and scattering magnetic skyrmions. Fig (a) highlights that the majority of the nanowire's magnetic moments is going out of the plane of the figure except at the core of the skyrmion (red region), where they are pointing in the opposite direction.…”
Section: Introductionmentioning
confidence: 66%
“…Our predictions to suppress the skyrmion Hall effect are summarized in the Figures 5 and 10. In a previous work [47], our team showed that spatial variations on the material parameters of the ferromagnetic nanotrack (exchange stiffness, saturation magnetization, magnetocrystalline anisotropy and Dzyaloshinskii-Moriya constants) can work as traps for pinning and scattering magnetic skyrmions. In that work, we showed that the skyrmion was attracted to a trap characterized by a local increase in the Dzyaloshinskii-Moriya constant (D > D), whereas the skyrmion was repelled from a trap characterized by a local reduction in the Dzyaloshinskii-Moriya constant (D < D).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It is also possible to examine skyrmion dynamics using neutron scattering [45], x-ray diffraction [46], and changes in the noise fluctuations as a function of drive [47,48].Due to their stability, size scale, and manipulability, skyrmions are very promising candidates for a variety of applications including memory, logic devices, and alternative computing architectures [49,50]. The capability to precisely control the direction, traversal distance, and reversibility of skyrmion motion could open up new ways to create such devices, and there are already a number of proposals for controlling skyrmion motion using structured substrates such as race tracks [49,51,52], periodic modulations [53], or specially designed pinning structures [54][55][56][57][58]. One proposal for controlling skyrmion motion involves having the skyrmions interact with a two dimensional periodic substrate of the type that has already been realized for colloidal particles and vortices in type-II superconductors, and there are existing experimental realizations of skyrmions interacting with two-dimensional (2D) anti-dot arrays [59].A key feature that distinguishes skyrmions from colloids and superconducting vortices is the strong non-dissipative Magnus component in the skyrmion dynamics caused by topology [34,36,60].…”
mentioning
confidence: 99%
“…In previous works, our group observed that the local decrease (increase) of the exchange stiffness constant acts as an attraction (repulsion) pinning center to a vortex, domain wall or skyrmion [33,34,41,42]. In two recent works [43,44] we showed other three ways to build magnetic skyrmion traps using magnetic defects, as variation in magnetocrystalline anisotropy, in DM interaction and in dipolar constant. Recently, we proposed several ways of suppression the skyrmion Hall effect in ferromagnetic nanotracks with their magnetic properties strategically modified [44].…”
Section: Introductionmentioning
confidence: 90%